(untitled) (Research, Society and Development, 2023)
Objectives: To demonstrate whether there was an increase and/or aggravation in cases of mental disorders during the COVID-19 pandemic among medical students at an institution in countryside of Goiás. Methodology: This is a cross-sectional, exploratory and quantitative study, carried out through the Google Forms platform, completed by 354 medical students from the 1st to 12th period, including basic, clinical and internship cycle, from an institution in the interior of Goiás. Results: 269 students denied having developed any kind of mental disorder during the pandemic. 85 students confirmed having some disorder, the main ones being: generalized anxiety, major depressive disorder, attention deficit hyperactivity disorder, panic syndrome and bipolar affective disorder. They were also asked about the concern with the post-pandemic routine, of which 299 students said they were worried. Conclusion: Even with an increase in cases of psychiatric illnesses, in this academic community, there was no development, worsening or association with any mental disorder in a significant way. Even so, those who had any kind of disorder or anxiety in the face of the COVID-19 pandemic deserve attention, as mental disorders, in general, are public health problems, and little is known about the future damages that the COVID-19 pandemic may cause.